Is Douglas Fir [Pseudotsuga menziesii (Mirbel) Franco] Invasive in Central Europe? A Case Study From South-West Germany - Lange, Felix; Ammer, Christian; Leitinger, Georg; Seliger, Alexander; Zerbe, Stefan (Frontiers in Forests and Global Change, 2022)
Worldwide, forestry must face several challenges during the UN Decade on Ecosystem Restoration. The decline of biodiversity and ecosystem services, ongoing deforestation, climate change, and biological invasions must be mitigated with forest restoration and by applying sustainable forest management. Experiences with the integration of non-native tree species into forest management in many parts of the world show benefits but also trade-offs regarding sustainability. In Central Europe, Douglas fir (Pseudotsuga menziesii (Mirbel) Franco), originating from Northern America, has been introduced by forestry and managed for more than one and a half centuries. Growth characteristics, drought tolerance, and timber quality are major reasons which make this tree species attractive for forestry and wood industry. Whether Douglas fir might be invasive with potential trade-offs regarding biodiversity, uncontrolled regeneration, and spread is not yet fully understood and controversially debated. We investigated the regeneration of Douglas fir in the Spessart mountains, a vast woodland in south-western Germany which has a considerable cover of anthropogenic coniferous afforestations. We sampled the regeneration of Douglas fir by differentiating height growth classes in various forest-stand types, taking the distance from mature mother trees, abiotic site conditions (e.g., water balance, soil properties), light supply, forest-stand characteristics, ground vegetation, and browsing pressure into account. Also integrating the individual regeneration of the accompanying tree species, we applied multivariate analyses. Most of our investigated variables did not show a significant correlation with Douglas fir regeneration. However, results point to a positive relationship of spontaneous Douglas fir regeneration at moist and light sites as well as in close distance to potential seed trees. The analysis of the current invasion potential did not reveal a major risk under the given site conditions in the study area.